ANALISIS KINERJA KEUANGAN PERUSAHAAN MENGGUNAKAN METODE ECONOMIC VALUE ADDED (EVA) DENGAN MICROSOFT VISUAL BASIC - Suhartono, Suhartono (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2012)
Competition is increasingly competitive business world in all fields require firms to further improve its performance. Economic Value Added (EVA) is one appropriate method for measuring a company's financial performance. Company's financial performance is the company's achievements in the transaction or the business as measured by capital adequacy, liquidity andprofitability. EVA aims to assess the financial performance of companies that are indicators of the addition of the value of an investment in the form of income and value-based. EVA is useful for measuring the performance of a company that can stand alone without the need for other measures in the form of comparisons with similar companies or to analyze the trend (trend). Oneof the advantages of EVA is used as the basis for assessment of bonuses to employees, especially in the division that provides EVA is more that can be said that the EVA running stakeholders satisfaction concepts. The disadvantage of EVA are based on the belief that investors rely heavily on fundamental approach in reviewing and making decisions to buy and sell particular stocks.With the tool (tools) Ms. Visual Basic Programming, analysis of company financial performance using Economic Value Added (EVA) can more quickly and accurately.